Kesulitan Memahami Faktor-Faktor Yang Mempengaruhi Kesetimbangan Kimia Pada Siswa SMA Negeri Di Kota Palangka Raya - Seliwati Seliwati; Suandi Sidauruk; Akhmad Damsyik (Jurnal Ilmiah Kanderang Tingang, 2020)
This study aims to describe the difficulties of class XI MIPA State Senior High School students in Palangka Raya City in understanding the concept of factors that affect chemical equilibrium and the application of the principle of equilibrium reactions in industry at a microscopic level which is applied in the form of images. The research subjects were 928 students of class XI MIPA Senior High School in Palangka Raya City for the 2017/2018 Academic Year. Students' difficulties were investigated using a test instrument for understanding the factors that affect chemical equilibrium and the application of the principle of equilibrium reactions in industry. The instrument used is a multiple choice written test with five answer choices and five closed reasons and interviews. The results showed that students had difficulty understanding the concept of factors that affect chemical equilibrium at the microscopic level which were applied in the form of pictures and identified the causes of student difficulties, namely: (1) Explaining the effect of changes in concentration on shifts in chemical equilibrium by 62.82%, students consider the addition of the concentration of similar ions into the solution causes the ions to increase; (2) Explaining the effect of temperature changes by 55.28%, students assume that if the temperature is lowered the reaction shifts to endothermic reactions and vice versa (students do not understand the characteristics of exothermic/endothermic reactions and their relationship to temperature changes); (3) Explaining the change in volume of 61.96%, students assume that if the volume is reduced the equilibrium reaction shifts towards the component of the large reaction coefficient and vice versa; (4) Explaining the effect of changes in pressure by 53.56%, students assume that if the pressure is increased the reaction shifts to a large component of the reaction coefficient and vice versa; (5) Explaining the principle of an equilibrium reaction in an industry of 66.06%, students assume that by adding pressure to an exothermic reaction, the reaction shifts towards the reactants.